Brazilian Size Distribution of Income - Fishlow, Albert (American Economic Review, 1972)
The two postwar decades have resolved definitively the capacity of developing nations to expand at rates in excess of 2 percent per capita. Yet it has become increasingly apparent that such a yardstick is an inadequate measure of performance. Here I examine another and more neglected dimension of development, the distribution of income. My objectives are fourfold: to describe briefly the procedures used to derive an estimated income distribution for Brazil for 1960;1 to discuss the profile of poverty as it presents itself in a developing country; to indicate the factors operating to produce skewness in the Brazilian distribution; and to assess, in light of these and governmental policy measures in the 1960's, the apparent changes between 1960 and 1970.